MENGENAL PUBLIC SPEAKING : KETRAMPILAN PENTING UNTUK ANAK USIA DINI DI TAMAN KANAK-KANAK - Dayati Erni Cahyaningrum; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Public speaking is an important skill for everyone, including young children, in developing this skill, of course you need the help of a teacher. The problem that occurs when developing skills is shyness and teachers rarely teach these skills during learning. The aim of this research is to determine public speaking skills for young children in Kindergarten with a qualitative research type using interview data collection to find out teachers' views regarding the concept, whether or not the introduction of public speaking in kindergarten is suitable, methods, difficulties and efforts made by teachers to overcome difficulties and expectations for the introduction of public speaking in kindergarten, observation of public speaking skills in class from a list of statements that have been designed, and documentation of activities and learning plans. Data analysis carried out in the form of Miles and Huberman techniques was collected, explained and concluded. The research results show that with the introduction of public speaking the teacher already understands the concept of introducing public speaking, there are efforts to introduce it in class in the form of discussions, role models, providing motivation, simple and clear pronunciation. Furthermore, teachers are able to overcome existing problems related to public speaking for early childhood skills so that they gain the benefits of being independent, brave, self-confident, and optimizing language development. However, the introduction of public speaking is influenced by the teacher's experience in teaching in class to optimize the introduction of this skill.Keywords: public speaking 1, children 2, teacher 3